Keberadaan Grup Karawitan Cikal Laras di Kabupaten Karanganyar Jawa Tengah - Anantama Mutaqim (SELONDING, 2018)
Group Cikal Laras domiciled in the Karangpandan district of Karanganyar district is a group of music that is active in developing a kind of music especially musical. Pangrawit is composed of the children SMP, SMA, SMU/K and Students. Activity undertaken by the group is to fill the stage held by the community and agencies. Wrong one of the music that is processed by the group Cikal Laras Gendhing Cakra that combines several forms of musical gendhing such as lancaran, ladrang, sampak, monggang and gangsaran. Presentation is performed in an instrumental manner that is played by young people so it looks harmonious. Cikal Laras group by using qualitative methods. This is done to see a phenomenon that exists about a group of music with players who are mostly young people in processing a cultivation. Meaning implied in this study is more directed to the existence of the group so it is still in demand by people in Karanganyar regency of Central Java. Existence of Cikal Laras group is still needed by the community in Karanganyar regency in enjoying or appreciating a form of musical dish especially karawitan. Creativity generated by this group makes the continuity of the show is increasing so that it can support the continuity of the group.